Odpowiedzi

2010-03-10T20:18:13+01:00

a) 8a+9=8*-2+9=-16+9=-7
b) -z+5t-1=-5+5*0,1-1=-5+0,5-1=-5,5
c) 5x-y=5*0,2+1=2
2010-03-10T20:19:10+01:00
A)2a+3-a+6+7a=2*2+3-2+6+7*2=4+3-2+6+14=25
b)2z+t-3z+4t-1=2*5+0.2-3*5+4*0.2-1=10+0.2-15+0.8-1=-5
c)13x-2y+7-9x+y-4+x-3=13*0.2-2*(-3)+7-9*0.2+(-3)-4+0.2=2.6+6+7-1.8-3-4+0.2-3=4
2010-03-10T20:59:03+01:00
A)2a+3-a+6+7a dla a= 2
8a+9
8*2+9=16+9=25

b)2z+t-3z+4t-1 dla z= 5 i t=0,2
-z+5t-1
-5+5*0,2-1
-5+1-1=-5

c)13x-2y+7-9x+y-4+x-3 dla x=0,2;y= - 3
5x-y+0
5*0,2+3
1+3=4

1 5 1